2017
DOI: 10.1038/srep44031
|View full text |Cite
|
Sign up to set email alerts
|

Widespread platinum anomaly documented at the Younger Dryas onset in North American sedimentary sequences

Abstract: Previously, a large platinum (Pt) anomaly was reported in the Greenland ice sheet at the Younger Dryas boundary (YDB) (12,800 Cal B.P.). In order to evaluate its geographic extent, fire-assay and inductively coupled plasma mass spectrometry (FA and ICP-MS) elemental analyses were performed on 11 widely separated archaeological bulk sedimentary sequences. We document discovery of a distinct Pt anomaly spread widely across North America and dating to the Younger Dryas (YD) onset. The apparent synchroneity of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 30 publications
9
62
0
Order By: Relevance
“…Their results indicate that extraterrestrial Pt settled out of the atmosphere into a 21-y interval of ice, rising 100 times above background at 12,822 5 140 cal BP, within the range 12,836-12,815 cal BP. Including this discovery, there have been multiple independent reports of Pt abundance peaks in the YDB layer at 22 sites in North America, Europe, and Asia: one site in Greenland (Petaev et al 2013b), one site in Russia (Andronikov et al 2014), four sites in Lithuania (Andronikov et al 2015), one site on the French-Italian border (Mahaney et al 2016b), two sites in the Netherlands (Andronikov et al 2016b), one site in Belgium (Andronikov et al 2016b), and 12 sites in the United States (Andronikov and Andronikova 2016;Moore et al 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Their results indicate that extraterrestrial Pt settled out of the atmosphere into a 21-y interval of ice, rising 100 times above background at 12,822 5 140 cal BP, within the range 12,836-12,815 cal BP. Including this discovery, there have been multiple independent reports of Pt abundance peaks in the YDB layer at 22 sites in North America, Europe, and Asia: one site in Greenland (Petaev et al 2013b), one site in Russia (Andronikov et al 2014), four sites in Lithuania (Andronikov et al 2015), one site on the French-Italian border (Mahaney et al 2016b), two sites in the Netherlands (Andronikov et al 2016b), one site in Belgium (Andronikov et al 2016b), and 12 sites in the United States (Andronikov and Andronikova 2016;Moore et al 2017).…”
Section: Resultsmentioning
confidence: 97%
“…The consequences of the impact (possibly a cometary airburst) were hypothesised to have destabilised the Laurentide Ice Sheet, cooled NH climate, and contributed to the megafaunal extinction characteristic of the period (Firestone et al, 2007;Kennett et al, 2009). The discovery of significant amounts of impactderived spherules scattered across North America, Europe, Africa, and South America at ∼ 12.80 ± 0.15 ka BP further supports the Younger Dryas Impact Hypothesis (YDIH) (Wittke et al, 2013), as does apparently extraterrestrially derived platinum, found initially in Greenland ice (Petaev et al, 2013) and subsequently globally (Moore et al, 2017), coincident with the YD onset. However, other research questions the evidence of an impact, focussing on perceived errors in the dating of the YD boundary layer (Holliday, 2015;Meltzer et al, 2014), the misidentification of terrestrially derived carbon spherules, shocked quartz, and nanodiamonds as extraterrestrial (Pinter et al, 2011;van Hoesel et al, 2015;Tian et al, 2011), the non-uniqueness of YD nanodiamond evidence , and inconsistencies regarding the physics of bolide trajectories and impacts (Boslough et al, 2013).…”
Section: Compatibility With Other Hypothesesmentioning
confidence: 58%
“…Despite many inconsistencies of the impact hypothesis, in particular concerning the physics of airbursts (Boslaugh et al 2013), geological evidence of such a catastrophic event is demonstrated by the dispersed glassy silicate and carbon spherules and nanodiamonds in the order of 10 million tons containing micron sized zircons and rutile, high-temperature melted glass, a wide spread platinum anomaly and occurrence of nanodiamonds ( Fig. 2) in eleven archaeological sites across North America (Bunch et al 2012;Moore et al 2017) and in the Greenland ice (Kennett et al 2009;Kurbatov et al 2010 Wittke et al (2013); Kinzie et al (2014).…”
Section: A Meteorite Impact As Trigger Of the Onset Of The Younger Dryasmentioning
confidence: 99%